Controlling Invasive Exotic Plants in North Florida Forests - Chris Demers; Alan Long (EDIS)
This document is SS-FOR-19, one of a series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published in June 2002.